5G TARMOQLARINI LOYIHALASH VA MODELLASHTIRISH: ARXITEKTURALAR, ASOSIY ISHLASH KO‘RSATKICHLARI - Abilova , Raykhon (Techscience uz - Topical Issues of Technical Sciences, 2025)
5G networks focus on meeting requirements such as wide coverage, high transmission rates, low latency, and device density. This article will analyze the main architectural approaches to the design and modeling of 5G networks, the main indicators (KPIs), as well as the problems encountered in practical design. Through Model and simulation tools, the relationship between architectural and functional parameters is demonstrated. As well as suggestions for matching various services, resource efficiency, and network slice (slices) management.